The beauty of pediatric musculoskeletal ultrasound - Drakonaki, Elena E; Adriaensen, Miraude; Simoni, Paolo; Aparisi Gomez, Maria Pilar (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Ultrasound is a powerful technique in pediatric imaging and musculoskeletal (MSK) imaging in many specific clinical scenarios. This article will feature some common and less common spot diagnoses in pediatric musculoskeletal ultrasound.Cases were collected by members of the Educational Committee of the ESSR (European Society of musculoSkeletal Radiology) and the Pediatric Subcommittee of the ESSR with expertise in musculoskeletal ultrasound.Fifteen clinical entities are discussed based on the features that allow diagnosis by ultrasound.Clinical history, location, and ultrasound appearance are the keys to spot diagnoses when performing pediatric musculoskeletal ultrasound.
Keywords: ultrasound; soft tissues; diagnostic radiology